Evaluación de tres selladores de barrera para el control de células somáticas e incidencia de mastitis en bovinos de leche en San Rafael de Vara Blanca, Heredia - Valverde-Rodríguez, Efrén (Instituto Tecnológico de Costa Rica, 2016)
The study evaluated the effectiveness of three barrier sealants for the somatic cell count (SCC) and the incidence of mastitis in dairy cattle. The study took place in Vara Blanca Agricultural Farm located in San Rafael, Vara Blanca, Heredia, Costa Rica. The evaluation period was from March 8 to May 27 2016, during 60 days approximately. The objectives of this research were to check the barrier sealant’s composition effect over the somatic cell control according to the number of births and the breastfeeding period as well as the effect of the composition of the barrier sealant over the incidence of mastitis according to the number of births and the breastfeeding period. A total random design was used with factorial arrangement and an odd number of repetitions for the data analysis. There were 8 samplings done with 7-day intervals. The samples were tested to determine quantitatively the somatic cell count (SCC) using a Fossomatic 400 counter; the California Mastitis Test (CMT) was applied to determine the incidence of mastitis (IM). It was found that once the SCC was assessed, there was no treatment effect, according to the number of births (P=0,0510); however, differences were found according to the breastfeeding period (P=0,001). For the IM variable significant differences were found between the treatment and the number of births (P=0,0036) but it was not the case of the breastfeeding period (P=0,1161). The lowest average of SCC during the study period was the Oxiclor-Gel® treatment (91 833 cell/ml of milk). The study concluded that the most efficient somatic cell control and IM treatment is the Oxiclor-Gel®.
Trabajo Final de Graduación (Licenciatura en Ingeniería en Agronomía). Instituto Tecnológico de CostaRica. Escuela de Agronomía. 2016
Keywords: Bovinos; Lactancia; Parto; Enfermedades del ganado; Análisis de datos; Research Subject Categories::VETERINARY MEDICINE